Electrolyte dysfunction in myocardial infarction patients - S., Hariprasad; M., Basavaraj (International Journal of Advances in Medicine, 2018)
Background: Myocardial Infarction (MI) is the term given for a state of myocardial necrosis which is secondary to an acute interruption of the coronary blood supply. Severity is dependent on level of occlusion, length of time of occlusion and presence or absence of collateral circulation. Myocardial infarction is now considered part of a spectrum referred to as acute coronary syndrome. It is a spectrum of acute myocardial ischemia that also includes unstable angina (STEMI) and non-ST segment elevation myocardial infarction (NSTEMI). The changes in serum electrolytes were studied in this study with a special focus on sodium and potassium serum levels in patients suffering from AMI. Hence, the aim of the study was to examine the changes in serum electrolytes among AMI patients and then comparison was done with the healthy persons. Methods: The study comprised of 80 subjects, which were divided equally into study group and control group. The study group comprised cases of confirmed diagnosis of recent onset of AMI. Clinical data was collected using interviewing questionnaires. The blood samples of both groups were analysed for serum electrolytes (Na+, K+, Cl-, Ca+ and Mg+) with the help of ion sensitive electrode analyser along with quality control sera. Results: There was statistically significant decrease in sodium and potassium levels in AMI patients. It was found that there was decrease in sodium serum levels in AMI patients suffering with hypertension. Potassium levels were increased in AMI patients suffering from Diabetes Mellitus and Hypertension, which was found to be statistically significant. Conclusions: Hyponatremia and hypokalemia are indicators of acute myocardial infarction. Serum sodium and potassium levels are prognostic indicators, i.e., rise in sodium levels after initial fall was indicative of clinical improvement. Therefore, estimation of sodium and potassium level in acute MI patients can help assess their prognosis.